Outcome of relapsed and refractory nodular lymphocyte‐predominant Hodgkin lymphoma: a North American analysis. (31st January 2021) - Strati, Paolo; Cheng, Phoebe T. M.; Steiner, Raphael E.; Alcedo Andrade, Pedro E.; Feng, Lei; Sano, Dahlia; Rao, Veeramaneni A.; Singh, Prachee; Miranda, Roberto; Gunther, Jillian R.; Pinnix, Chelsea C.; Dabaja, Bouthaina S.; et al.
Summary: Nodular lymphocyte‐predominant Hodgkin lymphoma (NLPHL) is a rare entity, with limited data on the outcome in the relapsed/refractory setting. We evaluated the outcome of all patients diagnosed between 04/1979 and 01/2019 with relapsed or progressive NLPHL after initial active therapy at two institutions, refractory disease being defined as lack of response to treatment and/or relapse within three months of treatment. NLPHL patients with histological evidence of transformation at time of first relapse or progression were excluded. In total, 69 patients with recurrent NLPHL were included in the study. After a median follow‐up after initial diagnosis of 14 years (range, 0·5–46 years), median progression‐free survival after front‐line treatment (PFS‐1) was four years. Second‐line therapy included chemotherapy in 28 (41%) patients, biological therapy (rituximab, lenalidomide or brentuximab vedotin) in 14 (20%), high‐dose chemotherapy followed by autologous stem cell transplant in 14 (20%) and radiation therapy (RT) alone in 10 (15%). The five‐year PFS after second‐line therapy (PFS‐2) was 68% [95% confidence interval (CI), 54–79%] but the five‐year overall survival (OS) after second‐line therapy (OS‐2) remained excellent, at 94% (95% CI, 85–99%). Due to excellent outcome in case of recurrence, studies aimed at characterizing its biology to guide therapy de‐escalation are needed.